Atividades metabólicas e endócrinas de adipócitos extraídos do tecido adiposo subcutâneo e visceral de animais obesos induzidos por dieta hiperlipídica e suplementados com ácidos graxos ômega-3 - Cunha, Roberta Dourado Cavalcante da [UNIFESP] (2015)
The efforts dedicated to finding the cure for obesity and associated disorders lead to an intense interest in adipocyte metabolism. The consumption of ω-3 fatty acids (ω-3 FA) presents beneficial effects on changes caused by obesity. The aim of this study was to characterize the metabolic and endocrine changes of isolated isolated adipocytes from obese mice induced by high fat (HF) diet, supplemented or not with fish oil rich in ω-3 FA (EPA/DHA, 5:1) with emphasis on the differential response of subcutaneous and visceral adipose deposits, inguinal (ING) and retroperitoneal (RP) region, respectively. For this, C57BL/6 males mice 8 weeks-old, were divided into 4 groups: CO, animals fed with control diet (9% of lipids); CO + ω-3, fed with control diet supplemented with ω-3 FA; HF, fed with HF diet (59% of lipids); and HF + ω-3, fed with HF diet supplemented with ω-3 FA. The animals were evaluated for food intake, body mass, glucose tolerance test (GTT) and insulin (ITT), insulin resistance and plasma lipid profile. From ING and PR isolated adipocytes, we evaluated the glucose uptake, lipogenesis, de novo synthesis of FA, lipolysis and the gene and protein expression of adipokines. The animals fed with the HF diet presented a higher body weight, glucose and insulin intolerance and insulin resistance, increase in liver weight and a higher serum concentrations of total and LDL cholesterol. It was also observed a greater weight of ING and PR adipose tissues, as well as an increament in the size of their cells (hypertrophy). The fish oil per se, administered in a prevention model (i.e., the ω-3 FA supplementation starting 4 weeks before the induction of obesity) in mice fed with CO diet, had no effect on body weight, blood glucose and insulin, or on the metabolic activities (lipolysis, lipogenesis, glucose uptake), as well as on the secretion or gene expression of cytokines, in isolated adipocyes. On the other hand, the fish oil showed an anti-obesogenic action associated to beneficial effects on dyslipidemia, insulin resistance and dysfunction of adipocytes arising from HF diet. HL diet altered differently the functions of RP and ING adipocytes, since RP adipocytes became potentially lipolytics and producers of pro-inflammatory cytokines with a reduced function on the de novo synthesis of FA, while ING adipocytes showed a decrease on glucose uptake and on secretion of the anti-inflammatory cytokine adiponectin, besides contributing on the secretion of TNFα and IL-6 citokines. Moreover, our results show an important and differential role of adipocytes per se, positively correlated with its hypertrophy, on the secretion of cytokines, contesting the exclusive importance given to immune cells that infiltrate the white adipose tissue in conditions of obesity.